The Role of Peer Tutoring on Students’ Writing Skills: The Role of Peer Tutoring on Students’ Writing Skills - Labib Halim (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to test the role of peer tutoring on students' writing skills, especially in writing recount text. This study used experimental research design. The subjects of this study were second grade students of SMPN 1 Turi Lamongan, East Java, for the 2020/2021 academic year. The subjects in this study were 50 students taken from class VIII A and VIII B, which were then grouped into experimental and control groups respectively. The data of this study were taken from student test scores which were held at the end of the study and were analyzed using Independent T-test analysis. The results of data analysis showed that there was a significant effect on the implementing of peer tutoring on students’ writing skills. These results were obtained from the mean score of students’ tests from each group. The control group got an average score of 69.40, while the experimental group got an average score of 76.20.